SUSTAINABLE USE OF RECYCLED AGGREGATE IN CONCRETE - MISS. KALYANI RAMESH MAMDYAL; PROF. JAWALKAR G. C. (International Journal of Innovations in Engineering Research and Technology, 2021)
In this research study, Natural coarse aggregates are replaced by Recycled coarse aggregates (RCA) with various percentage of RCA i.e. 25%, 50%, 75%, 100%. An Experimental work was performed to determine the compressive strength of recycled coarse aggregate concrete and to compare them with those of concrete made using natural coarse aggregate.